1977
DOI: 10.1002/ijc.2910200205
|View full text |Cite
|
Sign up to set email alerts
|

Cellular cytotoxicity in vitro in transitional cell carcinoma of the human urinary bladder: 51Cr‐release assay

Abstract: The cytotoxicity in vitro of peripheral blood lymphocytes from 54 patients with transitional cell carcinoma of the urinary bladder (TCC-bladder) against a small panel of allogeneic target cells was studied by the "'Cr-release assay. Lymphocytes f r o m 20 patients with other neoplastic diseases, mainly urogenital cancers, were used as controls. Also included were lymphocytes from 24 healthy donors. Lymphocytes f r o m individual donors of all three groups were frequently cytotoxic t o any one of the target cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1977
1977
1981
1981

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…As already stated, this was not an unexpected finding since the treated TCC patients studied here were a heterogeneous group. In this respect, the results obtained with IgG from either treated or untreated TCC patients are very similar to those obtained in previous studies of the cytotoxicity of their lymphocytes (Troye et al, 1977a;1980a).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As already stated, this was not an unexpected finding since the treated TCC patients studied here were a heterogeneous group. In this respect, the results obtained with IgG from either treated or untreated TCC patients are very similar to those obtained in previous studies of the cytotoxicity of their lymphocytes (Troye et al, 1977a;1980a).…”
Section: Discussionsupporting
confidence: 89%
“…The cells were propagated in Parker's medium 199, supplemented with glutamine, streptomycin, penicillin and 10 % heat-inactivated fetal bovine serum (FBS). For details, see Troye et al (1977a;1980a). All sera used for preparing IgG were fractionated either immediately after withdrawal from the donor or after a few days' storage at 4" C. No frozen sera were used.…”
Section: Target Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although impairment of SLMC in cancer patients has been reported by some investigators [2,7,19,31], others have found these functions normal [8,17]. Selective enhancement of SLMC against certain target cells has also been reported [2,14,32]. Our results indicate that PBL from patients with TCC did not exhibit a decline in overall spontaneous cytotoxic activity compared with lymphocytes of a control group.…”
Section: Discussioncontrasting
confidence: 42%
“…This observation has since been supported by a number of authors [1,15,32]. This in vitro cytotoxicity is, to a certain extent, influenced by tumor mass and various treatments.…”
Section: Introductionmentioning
confidence: 56%